Analysis of Flower Color Variation in Carnation (Dianthus caryophyllus L.) Cultivars Derived from Continuous Bud Mutations - Morimoto, Hayato; Narumi-Kawasaki, Takako; Takamura, Takejiro; Fukai, Seiichi (Horticulture journal, 2019)
Bud-mutation carnation cultivars of the “MINAMI series” have a diversity of flower color in which the directions of bud sports are recorded. ‘Poly Minami’, which is the origin of the “MINAMI series”, produced the eight cultivars with various petal colors through continuous bud mutations. Flavonoid pigments analysis showed that the flower color variation is produced by the difference in the quantitative ratios of pelargonidin-typed anthocyanin and chalcononaringenin 2′-O-glucoside (Ch2′G). Acyanic cultivars; ‘Poly Minami’, ‘Lemon Minami’ and ‘Vanilla Minami’ had Ch2′G showing a yellow coloration as a major flavonoid with different concentrations in the petals. Cyanic cultivars with pinkish petals; ‘Orange Minami’, ‘Minami’, ‘Passion Minami’ and ‘Feminine Minami’ had different ratios of 3,5-di-O-(β-glucopyranosyl) pelargonidin 6′′-O-4,6′′′-O-1-cyclic malate (Pg3,5cMdG), showing a pink coloration, and Ch2′G as major flavonoids in the petals. The variegated cultivar ‘Sakura Minami’, with deep pink sectors and flecks on pale pink petals, accumulated a small amount of Pg3,5cMdG. The red-flowered cultivar ‘Tommy Minami’ accumulated pelargonidin 3-O-malylglucoside (Pg3MG) showing a red coloration as a major anthocyanin in the petals. The gene expression analysis through flower-bud development showed that the ratios of Pg3,5cMdG and Ch2′G are produced by the difference in the expression levels of flavonoid biosynthesis-related genes; the dihydroflavonol 4-reducatse gene (DFR), the chalcononaringenin 2′-O-glucosyltransferase gene (CHGT2) and the chalcone isomerase gene (CHI2) and the acyl-glucose-dependent anthocyanin 5-O-glucosyltransferase gene (AA5GT) and an anthocyanin transportation-related gene; the glutathione S-transferase-like gene (GSTF2). This study revealed that the flower color variations in the “MINAMI series” are caused by genetic and metabolic changes associated with flavonoid biosynthesis and identified five candidate genes for flower color changes in the “MINAMI series”.